Obesity: The Octopus in the Room - Sanjay Kalra; Madhur Verma; Nitin Kapoor (Journal of the Pakistan Medical Association, 2024)
The octopus, an eight-legged invertebrate, is known for its unique biology, as well as its intelligence. Famed for its mystique and mysteriousness, the octopus is an emblem of the wonders of nature. Octopuses can bite humans, can secrete fatal neurotoxins (tetrodotoxin), and are a cannibalistic species. While they are a benthic species, living in deep seas,1 their imagery abounds in multiple places. Continued...